Analisis Putusan Nomor 259/Pdt.Sus-PKPU/2022/PN Jkt Pst tentang Pemeriksaan Penundaan Kewajiban Pembayaran Utang yang Diputus Melebihi Jangka Waktu: Analysis of Decision Number 259/Pdt.Sus-PKPU/2022/Pn Niaga Jkt Pst concerning Postponement Debt Payment Obligations Decided to Exceed the Period - Muhammad Raja Akbar Rachman; Ning Adiasih (Reformasi Hukum Trisakti, 2024)
The regulation concerning the timeframe for PKPU (Suspension of Debt Payment Obligations) decisions is intended to ensure business certainty for the debtor. However, in practice, there are instances where court decisions do not adhere to these regulations. This study addresses two main issues: first, the examination timeframe for PKPU cases in Decision Number 259/Pdt.Sus-PKPU/2022/PN Niaga Jkt Pst. in relation to Article 225, paragraph (3) of the PKPU Law, and second, the legal remedies and impacts if errors are found in the court's decision regarding the PKPU case under the same decision, according to the PKPU Law. The research employs normative legal writing methods with a descriptive approach, using secondary data including primary and secondary legal materials, and draws conclusions through deductive reasoning. The findings indicate that in Decision Number 259/Pdt.Sus-PKPU/2022/PN Niaga Jkt Pst., there was a judicial error because the PKPU request, made by a creditor, was decided within 69 days, which is inconsistent with the prescribed timeframe. If such an error occurs, the debtor can pursue cassation as a legal remedy, in line with the Constitutional Court Decision 23/PUU-XIX/2021.